NAVIGATING THE ENGLISH PROFICIENCY TEST: A MIXED-METHOD STUDY ON EAST TEST-TAKERS' CHALLENGES AND COPING STRATEGIES - Nabila, Desy Ainun; Maulina, Maulina; Faridawati, Faridawati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Tests of English proficiency are critical entry points in higher education, yet many students struggle to demonstrate their actual competence. This study employs an explanatory sequential mixed-methods design to investigate the linguistic and non-linguistic difficulties students encounter during the English as a Standardized-Test (EAST) at Universitas Muhammadiyah Kendari. Quantitative data from recent test scores were analyzed using descriptive statistics, revealing performance gaps with scores ranging from 35–55 (Level 2) to 67–86 (Level 3). To support and explain these results, qualitative data were gathered through reflective journals and interviews with seven purposively selected participants. Thematic analysis revealed that phonological shock from fast British-accented audio and stringent regulations dominated linguistic obstacles. Non-linguistic challenges included significant test anxiety and academic identity threat, where students feared low scores would invalidate their status as English majors. Despite these pressures, participants showed learner agency through coping mechanisms like physiological grounding and digital self-remediation. The study concludes that success in institutional exams depends on a combination of linguistic ability, psychological resilience, and environmental comfort. Recommendations include integrating metacognitive training and improving exam acoustics to enhance performance.